2017
DOI: 10.1038/s41598-017-11514-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities in placentas from term normal pregnancy exhibit spatially variable profiles

Abstract: The placenta is the principal organ nurturing the fetus during pregnancy and was traditionally considered to be sterile. Recent work has suggested that the placenta harbours microbial communities, however the location and possible function of these microbes remain to be confirmed and elucidated. Here, we employed genomic DNA sequencing of multiple variable (V) regions of the bacterial 16S ribosomal gene, to interrogate microbial profiles in term pregnancies, from the basal plate, which is in direct contact wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
155
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 143 publications
(168 citation statements)
references
References 41 publications
(57 reference statements)
5
155
0
8
Order By: Relevance
“…In addition to immune cells, the placenta harbors a low abundance but metabolically rich microbiome 147 that varies from the decidua to basal plates to the fetal membranes. 148 This microbial community is disrupted with preterm labor, 149 PE 150 and gestational weight gain, 151 and pregravid obesity. 126 Some of these studies were carried out using placenta samples of preterm births; therefore, our understanding of the impact of pregravid obesity on microbial communities within the term placental decidua remains limited.…”
Section: Pregravid Obesity and Immune Adaptations In The Placentamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to immune cells, the placenta harbors a low abundance but metabolically rich microbiome 147 that varies from the decidua to basal plates to the fetal membranes. 148 This microbial community is disrupted with preterm labor, 149 PE 150 and gestational weight gain, 151 and pregravid obesity. 126 Some of these studies were carried out using placenta samples of preterm births; therefore, our understanding of the impact of pregravid obesity on microbial communities within the term placental decidua remains limited.…”
Section: Pregravid Obesity and Immune Adaptations In The Placentamentioning
confidence: 99%
“…In addition to immune cells, the placenta harbors a low abundance but metabolically rich microbiome that varies from the decidua to basal plates to the fetal membranes . This microbial community is disrupted with preterm labor, PE and gestational weight gain, and pregravid obesity .…”
Section: Introductionmentioning
confidence: 99%
“…We found a high prevalence of R. insidiosa, a waterborne environmental bacterium, in human BPs using multi-variable region 16S sequencing approach 19 . Other investigators have also identified Ralstonia spp.…”
Section: Discussionmentioning
confidence: 88%
“…Whether there are microbiota (live or simply DNA signatures) in the maternal-fetal interface remains mired in controversy. In the recent years, there has been a large number of studies, providing both sequencing and histological evidence, indicating microbial signatures 3,11,18,19,22,23,29 , while other studies have reported these signatures as likely DNA contaminants originating from the sample collection and/or the DNA extraction process, rather than the placenta itself [54][55][56][57] . Placenta location remains a key variable in the aforementioned studies given that that BP, PV and FM have distinct physiology and function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation